Model‐Based Optimization of a Photocatalytic Reactor with Light‐Emitting Diodes. Issue 10 (6th July 2016) - Khodadadian, Fatemeh; Poursaeidesfahani, Ali; Li, Zonghan; van Ommen, J. Ruud; Stankiewicz, Andrzej I.; Lakerveld, Richard
Abstract: The complicated interplay between mass and photon transfer within a photocatalytic reactor calls for an integrated design approach. A model‐based optimization approach for LED‐based photocatalytic reactors is presented. First, a model that describes the distribution of reactants and photons within a photocatalytic reactor is developed. Then, several design variables related to the reactor dimensions and light sources are optimized simultaneously using the photocatalytic degradation of toluene as a model system. The results demonstrate how different formulations of the problem can be used to either minimize the reactor cost or to obtain a specified concentration profile within the reactor. Abstract : An LED‐based photocatalytic reactor is modeled based on mass, momentum, and photon transfer equations. Different objective functions are formulated to find optimal values for reactor dimensions and the number and positioning of the light sources. The proposed approach facilitates the design of LED‐based photocatalytic reactors by optimization of mass and photon transfer simultaneously.